The positive feedback regulatory loop of miR160-Auxin Response Factor 17-HYPONASTIC LEAVES 1 mediates drought tolerance in apple trees. Issue 3 (6th December 2021) - Shen, Xiaoxia; He, Jieqiang; Ping, Yikun; Guo, Junxing; Hou, Nan; Cao, Fuguo; Li, Xuewei; Geng, Dali; Wang, Shicong; Chen, Pengxiang; Qin, Gege; Ma, Fengwang; et al.
Abstract: Drought stress tolerance is a complex trait regulated by multiple factors. Here, we demonstrate that the miRNA160–Auxin Response Factor 17 (ARF17)–HYPONASTIC LEAVES 1 module is crucial for apple (Malus domestica ) drought tolerance. Using stable transgenic plants, we found that drought tolerance was improved by higher levels of Mdm-miR160 or MdHYL1 and by decreased levels of MdARF17, whereas reductions in MdHYL1 or increases in MdARF17 led to greater drought sensitivity. Further study revealed that modulation of drought tolerance was achieved through regulation of drought-responsive miRNA levels by MdARF17 and MdHYL1; MdARF17 interacted with MdHYL1 and bound to the promoter of MdHYL1 . Genetic analysis further suggested that MdHYL1 is a direct downstream target of MdARF17. Importantly, MdARF17 and MdHYL1 regulated the abundance of Mdm-miR160. In addition, the Mdm-miR160-MdARF17–MdHYL1 module regulated adventitious root development. We also found that Mdm-miR160 can move from the scion to the rootstock in apple and tomato ( Solanum lycopersicum ), thereby improving root development and drought tolerance of the rootstock. Our study revealed the mechanisms by which the positive feedback loop of Mdm-miR160-MdARF17-MdHYL1 influences apple drought tolerance. Abstract : A positive feedback loop of microRNA160-Auxin Response Factor 17-HYPONASTIC LEAVES 1 influences apple drought tolerance by regulating root-development and drought-responsive miRNAs.